The effect of contralateral prophylactic mastectomy on breast‐related charges: A 5‐year analysis. Issue 1 (11th August 2018) - Smith, Jesse R.; Jaffe, Jennifer; Pruitt, Jaclyn; Yao, Katharine; Sisco, Mark; Kuchta, Kristine; Wang, Chi E.; Howard, Michael A.
Abstract : Background and Objectives: The purpose of this study was to determine charges following unilateral mastectomy (UM) and bilateral mastectomy (BM) for patients with unilateral breast cancer (UBC). We hypothesized that BM may be associated with fewer charges over time. Methods: A retrospective review was conducted of patients with UBC treated between 2006 and 2010 with UM and BM in a large healthcare system. Institutional billing data were investigated for 5 years postoperatively to calculate the immediate and subsequent charges of all inpatient and outpatient breast‐related care associated with the initial diagnosis for a subset of patients identified using propensity score matching method. Results: A subset of matched patients (n = 320) undergoing UM (n = 160) or BM (n = 160) were included in this analysis. At 1 year, there was a trend toward lower total charges following UM as compared with BM (median, $125 230 vs $138 467; P  = .6075). However, during years 2 to 5, total charges were significantly higher following UM vs BM ($22 128 vs $13 478; P  = .0116). Conclusions: While initially higher, overall charges for BM are lower than UM between 2 and 5 years out from surgery. Further study is necessary to determine if this trend is sustained over the long term. These data can inform patient decision making regarding mastectomy for their breast cancer.